Unlocking potential: integrating the natural and urban corridors of Brooklyn for economic, environmental, and social prosperity - Coetsee, Hanno (School of Architecture, Planning and Geomatics, 2025)
The urban landscape of Brooklyn presents a complex challenge in the form of an isolated neighbourhood and wetland, which demand innovative approaches for their integration into a unified natural and urban system. The heart of the issue is about striving for economic growth, preserving the environment, and promoting social inclusivity. This research project aims to address these challenges by: planting seeds of development across boundaries that's feed back into Koeberg corridor. Investigating the integration of the Zoarvlei wetlands. Providing equitable housing solutions to the residents of Brooklyn. The theoretical framework of the research is shaped by the concepts of densification and activity corridors, emphasizing the optimization of land use and the creation of vibrant, multifunctional spaces. The findings of this study will contribute to the field of urban design by providing instights, recommendations, and strategies for promoting sustainable urban development, enhancing community well-being, and creating inclusive neighbourhoods that are integrated into its bigger urban and natural systems.